Pendekatan Sainstifik Dengan Menggunakan Media Loose Parts Yang Berorientasi Pada Hots Dapat Meningkatkan Perkembangan Anak Pada Nilai Moral di TK Pelita Nusantara - Darmanina Lisanti; Eri Yanti; Endang Sulastri (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by the facts in the field which show that children's ability to use loose parts media oriented to HOTS can improve children's moral development with a scientific approach at Pelita Nusantara Tanjungpinang Kindergarten there are still many children who are not right when using it. The purpose of this study was to improve scientific skills with loose parts media in group A at Pelita Nusantara Kindergarten. The improved ability is to be able to use loose parts media oriented Hots on children's moral development. This type of learning improvement is done by Classroom Action Research (PTK) with two learning cycles. Research activities were carried out at Tanman Kanak-Kanak Pelita Nusantara in group A children totaling 12 children consisting of 7 boys and 5 girls. After carrying out learning improvement activities, the sauntifik approach by using loose parts media oriented to Hots in improving children's moral development at Pelita Nusantara Kindergarten is very appropriate because these diverse activities raise children's interest and children can actively participate in activities. Keywords: children's moral development, loose parts media, scientific approach model